High-phosphate induced vascular calcification is reduced by iron citrate through inhibition of extracellular matrix osteo-chondrogenic shift in VSMCs. (15th December 2019) - Ciceri, Paola; Falleni, Monica; Tosi, Delfina; Martinelli, Carla; Bulfamante, Gaetano; Block, Geoofrey A.; Messa, Piergiorgio; Cozzolino, Mario
Abstract: Background: High serum phosphate (Pi) levels strongly associate with cardiovascular morbidity and mortality in chronic kidney disease (CKD) patients with vascular calcification playing a major role in the pathogenesis of related cardiovascular disease. High-Pi challenged vascular smooth muscle cells (VSMCs) undergo simil-osteoblastic transformation and actively deposit calcium-phosphate crystals. Iron-based Pi-binders are used to treat hyperphosphatemia in CKD patients. Methods: In this study, we investigated the direct effect of iron citrate on extracellular matrix (ECM) modification induced by high-Pi, following either prophylactic or therapeutic approach. Results: Iron prophylactically prevents and therapeutically blocks high-Pi induced calcification. Masson's staining highlights the changes of muscular ECM that after high-Pi stimulation becomes fibrotic and which modifications are prevented or partially reverted by iron. Interestingly, iron preserves glycogen granules and either prevents or partially reverts the formation of non-glycogen granules induced by high-Pi. In parallel, iron addition is able to either prevent or block the high-Pi induced acid mucin deposition. Iron inhibited calcification also by preventing exosome osteo-chondrogenic shift by reducing phosphate load (0, 61 ± 0.04vs0, 45 ± 0.05, Pi vs Pi + Fe, p < 0, 05, nmol Pi/mg protein) and inducing miRNA 30c (0.62 ± 0.05 vs 3.07 ± 0.62; Pi vs Pi + Fe, p < 0.01, relative expression). Studying aortic rings, we found that iron significantly either prevents or reverts the high-Pi induced collagen deposition and the elastin decrease, preserving elastin structure (0.7 ± 0.1 vs 1.2 ± 0.1; Pi vs Pi + Fe, p < 0.05, elastin mRNA relative expression). Conclusions: Iron directly either prevents or partially reverts the high-Pi induced osteo-chondrocytic shift of ECM. The protection of muscular nature of VSMC ECM may be one of the mechanisms elucidating the anti-calcific effect of iron. Highlights: Iron citrate prophylactically prevents high-phosphate vascular calcification. Iron therapeutically blocks high-phosphate induced vascular calcification. Iron citrate partially reverts osteo-chondrocytic shift of extracellular matrix. Iron protects the muscular nature of vascular smooth muscle cells.